PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DENGAN MEDIA KARTU SOAL UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN PRESTASI BELAJAR SEJARAH - Aisah, Isnaini; S., Leo Agung; Herimanto, Herimanto (Candi, 2018)
The aims of this research are to improve the students? social skills and historical learning achievement through aplicating numbered head together (NHT) cooperative learning model by using question-card media in historical learning.This research used Classroom Action Research (CAR) method which was implemented in two cycles. Every cycle consists of planning, implementation, observation, and reflection. The subject of this is class X IPS 3 SMA N 1 Ngemplak which consists of 33 students. The data collection techniques of this research use observation, interview, questionnaire, test, and documentation. Test validity of data using triangulation techniques which are data and method triangulation. The data analysis used are comparative descriptive analysis model and interactive analysis model.  The results of this study show that; 1) The implementation of Numbered Heads Together cooperative learning model by using question-card can increase the students? social skills in class X IPS 3 SMA N 1 Ngemplak. This is indicated by the increasing percentages of the number of students? social skills with a high category in the pre cycle, which is 21,21%. In the first cycle, then increased to 51,52% and 81,82% in second cycle. In the percentages result, the students? number who have high social skills and the average percentage of social skills indicators have exceeded the target ?80%; 2) The implementation of Numbered Heads Together cooperative learning model by using question-card can improve the learning achievement of students class X IPS 3 SMA N 1 Ngemplak. This shows the increased percentage of students? learning mastery in each cycle. At pre cycle, percentage of the number of students who can reach the limit of the value of learning domination (KKM 75) is 54,55%. In the first cycle, percentage of the number of students who can reach the limit of the value of learning domination increased to 60,70% and 93,94% in the second cycle. The acquisition percentage of students? learning achievement completeness passed the target which is ?80%.